Antara Ilmu dan Algoritma: Etika Kecerdasan Buatan dalam Pendidikan Islam Perspektif Maqāṣid Al-Sharī’ah - Ahmad Sabri; Ahmad Sulhan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The penetration of Artificial Intelligence (AI) into Islamic educational systems necessitates an in-depth ethical inquiry. This article aims to analyze the ethical implications of AI use in Islamic education through the Maqāṣid Al-Sharī’ah framework as a comprehensive Islamic normative value system. Employing a qualitative-analytical approach based on library research, this article maps the potential and threats of AI against the five fundamental elements of maqāṣid. Findings indicate that while AI holds considerable promise in enhancing accessibility and personalized learning within madrasahs and Islamic boarding schools (pesantren), it simultaneously poses serious risks, including the erosion of theological authority, cognitive dependency, and digital inequity. To address these issues, this article contributes to the existing literature by establishing a novel, actionable ethical framework consisting of seven maqāṣid-based principles that bridge normative Islamic values with algorithmic practices. Practical implications in the form of policy recommendations for Islamic educational institutions, governments, and technology developers are also presented to ensure a balanced, maṣlaḥah-oriented AI governance in Islamic pedagogy.